Effects of biochar on the chemical changes and phase separation of bio-asphalt under different aging conditions. (1st August 2020) - Zhou, Xinxing; Zhao, Guangyuan; Wu, Shaopeng; Tighe, Susan; Pickel, Daniel; Chen, Meizhu; Adhikari, Sanjeev; Gao, Yangming
Abstract: Bio-asphalt replaced petroleum-asphalt for paving asphalt pavements, which is a technology with a wide range of application prospect. This work is aimed at improving the performance of aged bio-oil modified asphalt (bio-asphalt) for use in road pavement construction. Biochar and bio-oil are renewable resources and use in this research that are pyrolyzed from waste wood. The effects of different aging conditions on biochar-modified bio-asphalt and ordinary bio-asphalt were investigated in terms of their chemical functional groups, molecular formulas, radius distribution functions, rheological parameters, and phase separation. The aging conditions considered in this research are short-term aging, ultraviolet (UV) aging, pressure aging vessel (PAV), and low-temperature hardening. Biochar plays a significant role in the UV aging process. This study found that, with an increase in biochar modification, the alkyl group numbers increased and the sulfoxide and carbonyl numbers decreased during the aging process of bio-asphalt. It also shows that the inclusion of biochar improved the aging resistance of the bio-asphalt, but that biochar modification did not affect the bio-asphalt's low-temperature hardening performance. Four asphalt components were studied: saturates, asphaltenes, resins, and aromatics (SARA). The effects of biochar on saturates and aromatics were significant, and the biochar was able to adsorb these components. This study also found that, with an increase in UV aging and PAV, the phase separation grows. Highlights: Biochar and bio-oil are renewable resources, which were derived from sawdust. The chemical change and phase separation of biochar-modified bio-asphalt were investigated. The molecular model and numerical model of biochar-modified bio-asphalt were built.